2013
DOI: 10.1063/1.4802881
|View full text |Cite
|
Sign up to set email alerts
|

Structure of multi-wall carbon nanotubes: AA′ stacked graphene helices

Abstract: The structure of multi-wall carbon nanotubes has been attributed previously to disordered stacking of the graphene planes. Evidence is presented that the nanotubes analyzed in this paper occur with stacked graphene layers in the sequence of AA′, where alternate graphene planes are translated by half the hexagon width. We further present proof that the crystalline materials comprise graphene helices (∼5 nm in width), rather than in the form of a perfect tube. We also show that the structural model proposed here… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…The model was based on the currently accepted structure of turbostratic stacking of seamless concentric graphene sheets of multi‐wall carbon nanotubes (MWNTs). Recently, however, we have shown that MWNTs are composed of graphene helices with widths of approximately five nanometres . The structure of MWNTs was attributed to the helical growth of the AA’ stacked graphene ribbons as the minimum energy configuration in contrast to circular growth at the tube edges.…”
Section: Introductionmentioning
confidence: 99%
“…The model was based on the currently accepted structure of turbostratic stacking of seamless concentric graphene sheets of multi‐wall carbon nanotubes (MWNTs). Recently, however, we have shown that MWNTs are composed of graphene helices with widths of approximately five nanometres . The structure of MWNTs was attributed to the helical growth of the AA’ stacked graphene ribbons as the minimum energy configuration in contrast to circular growth at the tube edges.…”
Section: Introductionmentioning
confidence: 99%
“…With the progress in fabricating mono- and multilayer graphene3, unique Moiré patterns45678 are revealed arising from the atomic-resolution transmission electron microscopy (TEM) morphology with rotating angles between graphene planes (i.e., disorderly stacked), and are proved as the signature of disordered graphite. Recently, we have shown that AA’ stacking of graphene planes (where each graphene plane is shifted by 1/2 hexagon from zigzag AA stacking or by 1/4 hexagon from armchair AB stacking) exists, and may be the structure of multi-wall carbon nanotubes (MWNTs) (i.e., helically grown AA’ graphite)910. This AA’ stacking has possibly been interpreted previously as disordered turbostratic structure1112131415 due to the unique X-ray diffraction (XRD) pattern, lacking several peaks for AB graphite (but revealing two peaks at 2θ = 42.4° and 2θ = 77.6°) and further supported by an interlayer spacing of ~3.44 Å9101112131415.…”
mentioning
confidence: 99%
“…Recently, we have shown that AA’ stacking of graphene planes (where each graphene plane is shifted by 1/2 hexagon from zigzag AA stacking or by 1/4 hexagon from armchair AB stacking) exists, and may be the structure of multi-wall carbon nanotubes (MWNTs) (i.e., helically grown AA’ graphite)910. This AA’ stacking has possibly been interpreted previously as disordered turbostratic structure1112131415 due to the unique X-ray diffraction (XRD) pattern, lacking several peaks for AB graphite (but revealing two peaks at 2θ = 42.4° and 2θ = 77.6°) and further supported by an interlayer spacing of ~3.44 Å9101112131415. However, MWNTs do not reveal the unique Moiré patterns for disordered graphite, but reveal crystalline features.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The pristine tubules reveal the unique bamboo morphology1819 evident of our helical MWNTs18. With an hour of milling, the tubules were decomposed to graphitic nanoribbons whose thickness and width are ~5 nm, respectively (b).…”
Section: Resultsmentioning
confidence: 99%